Nutritional assessment in overweight and obese patients with metastatic cancer: does it make sense?. (30th October 2014) - Gioulbasanis, I.; Martin, L.; Baracos, V. E.; Thézénas, S.; Koinis, F.; Senesse, P.
Abstract : Overweight /obese cancer patients face significant risk of malnutrition and they should not be spared from regular nutritional screening/assessment. Malnourishment, in this particular cohort, is additionally associated with adverse survival. Abstract : Background: Obesity is causally related with tumor development, and thus, many cancer patients are overweight or obese at diagnosis. Whether these patients need regular nutritional assessment is not known. In the present study, we evaluated the utility of Mini Nutritional Assessment (MNA), a nutritional screening/assessment questionnaire, in overweight or obese patients with metastatic tumors. Patients and methods: Overweight or obese patients referred for initiation of systemic therapy in three cancer centers were eligible. Basic demographics and clinical data were recorded. MNA was completed at baseline and patients were divided into three groups: A (well nourished), B (at risk), and C (malnourished). Survival data were subsequently collected. The prevalence of malnutrition and prognostic significance were evaluated. Results: In total, 1469 patients with metastatic primaries were identified. Of them, 594 (41.9%) were overweight or obese and included in the analysis. According to MNA, almost 50% were at risk and around 12% were already malnourished at presentation. A significant difference in overall survival was found between groups [group A 17.8 (15.5–20.1) months, group B 8.2 (7.3–9.3) months, and group C 6.4 (3.2–9.6) months, P < 0.001]. Moreover, MNA was the only independent predictor of survival. Conclusions: Our findings support that a significant percentage of overweight or obese cancer patients may be at nutritional risk and this is moreover related with adverse prognosis. An MNA score could be used for the identification of this risk.